Interventions to reduce dependency in personal activities of daily living in community-dwelling adults who use homecare services: protocol for a systematic review - Whitehead, Philip J.; Drummond, Avril E.R.; Walker, Marion F.; Parry, Ruth H. (BioMed Central, 2013)
Background